Optimalisasi Pembelajaran Musik Melalui Kegiatan Ekstrakurikuler Dengan Pendekatan Apprenticeship Di MTsN 3 Kota Padang - Tantowi, Irvan; Hairi Dilfa, Alrizka (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2025)
Music learning in formal schools often faces limitations in terms of time, teaching staff, and supporting facilities. This study aims to examine how extracurricular choir activities at MTsN 3 Kota Padang can optimize music learning that has not yet been maximally carried out in formal classes. This research uses a qualitative approach with a case study method, involving observation, interviews, and documentation as data collection techniques. The results of the study indicate that regular vocal practice, consisting of guided practice and independent practice, makes a significant contribution to developing students' vocal and musical skills. In addition to technical aspects, this extracurricular activity also plays an important role in fostering discipline, teamwork, and self-confidence. The implications of this activity are very strategic in filling the gap in formal music education and contributing to the development of students' cognitive, affective, and psychomotor competencies. However, there are still constraints related to limited facilities and infrastructure as well as trainers for other branches of music. Recommendations are given to madrasahs, supervising teachers, and students to improve the quality and sustainability of music extracurricular activities. This study makes an important contribution to the development of music learning in the madrasah environment.